f(x)=7x^5+x^4-2x^3+4 g(x)=x^4+6×63-4x^2+2x-1 a.f(x)+g(x)=h(x) b.f(x)+h(x)=0 c.f(x)-g(x)=h(x) d.g(x)-h(x)=0

Question

f(x)=7x^5+x^4-2x^3+4
g(x)=x^4+6×63-4x^2+2x-1
a.f(x)+g(x)=h(x)
b.f(x)+h(x)=0
c.f(x)-g(x)=h(x)
d.g(x)-h(x)=0

in progress 0
Latifah 5 months 2021-04-17T01:41:14+00:00 1 Answers 16 views 0

Answers ( )

    0
    2021-04-17T01:42:58+00:00

    Giải thích các bước giải:

    a.Ta có:

    $h(x)=f(x)+g(x)$

    $\to h(x)=(7x^5+x^4-2x^3+4)+(x^4+6x^3-4x^2+2x-1)$ 

    $\to h(x)=7x^5+x^4-2x^3+4+x^4+6x^3-4x^2+2x-1$

    $\to h(x)=7x^5+x^4+x^4-2x^3+6x^3-4x^2+2x+4-1$

    $\to h(x)=7x^5+2x^4+4x^3-4x^2+2x+3$

    b.Ta có:

    $f(x)+h(x)=0$

    $\to h(x)=-f(x)$

    $\to h(x)=-(7x^5+x^4-2x^3+4)$

    $\to h(x)=-7x^5-x^4+2x^3-4$

    c.Ta có:

    $f(x)-g(x)=h(x)$

    $\to h(x)=(7x^5+x^4-2x^3+4)-(x^4+6x^3-4x^2+2x-1)$ 

    $\to h(x)=7x^5+x^4-2x^3+4-x^4-6x^3+4x^2-2x+1$

    $\to h(x)=7x^5+x^4-x^4-2x^3-6x^3+4x^2-2x+4+1$

    $\to h(x)=7x^5-8x^3+4x^2-2x+5$

    d.Ta có:

    $g(x)-h(x)=0$

    $\to h(x)=g(x)$

    $\to h(x)=x^4+6x^3-4x^2+2x-1$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )